UNIDROIT principles through international investment arbitration awards - Malaguti, María Chiara (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The International Institute for the Unification of Private Law - UNIDROIT will start in 2023, in collaboration with the ICC Institute of World Business Law, a project that will evaluate the most appropriate rules in investment contracts in the light of the evolution of the contents of these contracts and international investment law in general. A fundamental part of the analysis will be the verification of the application of the UNIDROIT Principles to these contracts. In preparation for this project, this contribution describes the use that has been made so far of the Principles by arbitral tribunals whose awards are public, revealing how many of the Principles’ rules apply to investment contracts, for example in relation to the principle of good faith, situations of hardship, renegotiation of terms and the calculation of damages. In addition, the arbitral awards commented upon, also reveal how they can be used as applicable law not only in case of specific choice of the parties, but also in case of lack of indication of applicable law, as well as a tool for interpreting national law. For these purposes, the awards described are divided in this contribution by category according to the role attributed to the Principles in each award. However, the same analysis can be read to verify, in relation to the investment contracts analyzed, which rules have been referred to and to what extent (and yet in some cases, for example when using the Principles to determine damages, in reality the latter have also been invoked in relation to investment treaties).The analysis provided in this contribution, which hopefully shall be expanded on the basis of the investment contracts subject of arbitration to which we shall be able to have access under the Project, can be considered as one of the starting points for the exercise that will be carried out in the coming months.